Endothelial Cell Inflammation and Barriers Are Regulated by the Rab26-Mediated Balance between β2-AR and TLR4 in Pulmonary Microvessel Endothelial Cells - Huaping Chen; Ming Yuan; Chunji Huang; Zhi Xu; Mingchun Li; Chun Zhang; Zhan Gao; Mingzhou Zhang; Jiancheng Xu; Hang Qian; Jiegen You; Binfeng He; et al. (Hindawi Limited, 2019)
Rab26 GTPase modulates the trafficking of cell surface receptors, such as G protein-coupled receptors including α2-adrenergic receptors in some cell types. However, the effect of Rab26 on β2-adrenergic receptor (β2-AR) trafficking or/and Toll-like receptor 4 (TLR4) expression in human pulmonary microvascular endothelial cells (HPMECs) is still unclear. Here, we investigated the role of Rab26 in regulating the expression of β2-ARs and TLR4 in HPMECs and the effect of these receptors' imbalance on endothelial cell barrier function. The results showed that there was unbalance expression in these receptors, where β2-AR expression was remarkably reduced, and TLR4 was increased on the cell membrane after lipopolysaccharide (LPS) treatment. Furthermore, we found that Rab26 overexpression not only upregulated β2-ARs but also downregulated TLR4 expression on the cell membrane. Subsequently, the TLR4-related inflammatory response was greatly attenuated, and the hyperpermeability of HPMECs also was partially relived. Taken together, these data suggest that basal Rab26 maintains the balance between β2-ARs and TLR4 on the cell surface, and it might be a potential therapeutic target for diseases involving endothelial barrier dysfunction.